Role of Rhodopsins as Circadian Photoreceptors in the Drosophila melanogaster - Pingkalai R. Senthilan; Rudi Grebler; Nils Reinhard; Dirk Rieger; Charlotte Helfrich-Förster (Biology, 2019)
Light profoundly affects the circadian clock and the activity levels of animals. Along with the systematic changes in intensity and spectral composition, over the 24-h day, light shows considerable irregular fluctuations (noise). Using light as the Zeitgeber for the circadian clock is, therefore, a complex task and this might explain why animals utilize multiple photoreceptors to entrain their circadian clock. The fruit fly Drosophila melanogaster possesses light-sensitive Cryptochrome and seven Rhodopsins that all contribute to light detection. We review the role of Rhodopsins in circadian entrainment, and of direct light-effects on the activity, with a special emphasis on the newly discovered Rhodopsin 7 (Rh7). We present evidence that Rhodopsin 6 in receptor cells 8 of the compound eyes, as well as in the extra retinal Hofbauer-Buchner eyelets, plays a major role in entraining the fly’s circadian clock with an appropriate phase-to-light–dark cycles. We discuss recent contradictory findings regarding Rhodopsin 7 and report original data that support its role in the compound eyes and in the brain. While Rhodopsin 7 in the brain appears to have a minor role in entrainment, in the compound eyes it seems crucial for fine-tuning light sensitivity to prevent overshooting responses to bright light.